Application of Expert Information in Combining Economic Forecasts - A. Surkov, Anton; N. Salin, Victor; G. Tretyakova, Olga; N. Prasolov, Victor; A. Dolbik-Vorobey, Tatiana; Ye. Danilina, Larissa (International Journal of Psychosocial Rehabilitation, 2020)
Subject: Combining forecasting is one of the current alternatives to improve the accuracy of economic forecasts. Nowadays there are quite a lot of different options for constructing weight coefficients for combining forecasts; however, all of them are primarily based on statistical characteristics used by particular predictive models and, in fact, do not resort to applying expert information. Yet it is difficult to disregard the lack of its application in social and economic forecasting. The expert information in forecasting is a significant factor affecting its accuracy in the time of the call for universal use of all available information on the processes and promotions of the economics of digitization, as well as in the conditions of the strong dependence of economic phenomena on external factors.Purpose: The consideration of the options for applying expert information in combining forecasts is of essential importance. Moreover, the process of construction of generalized integral indicators, which occurs directly with the use of expert information, is structurally close to the combining of forecasts.Methodology: The article discusses advantages and disadvantages of the most popular approaches for constructing integral indicators based on expert information, as well as the opportunity of using such approaches in combining forecasts; the authors also propose to consider an approach dissimilar to the traditional use of expert information.Result: All the presented approaches for combining forecasts with the use of expert information are summarized in a general table; the latter was designed to assist in interpreting the applicability of expert information in combining forecasts, as well as to identify the possible trends in improving the use of expert information in forecasting.Conclusions: Following the obtained data on the proposed methods for combining forecasts with the use of expert information, conclusions can be drawn about the feasibility of using one or another approach in order to improve the accuracy of economic forecasting.